Pigment concentration, photosynthetic performance, and fatty acid profile of sub-Antarctic brown macroalgae in different phases of development from the Magellan Region, Chile - Ziemann dos Santos, Marco Aurelio; de Freitas, Samantha Coelho; Berneira, Lucas Moraes; Mansilla Muñoz, Andres Omar; Astorga España, Maria Soledad; Colepicolo, Pio; Pereira de Pereira, Claudio Martin (My University, 2019)
Macroalgae Durvillaea antarctica, Lessonia flavicans, and Macrocystis pyrifera in distinct development phases from the ecoregion of Magellan (Chile) were analyzed by pulse amplitude modulated fluorometry under eight irradiation conditions (11 to 490 mu mol photons m(-2) s(-1)). Pigmentation was assessed by UV/Vis spectrophotometry (400 to 700 nm), and fatty acid (FA) profile was determined by gas chromatography using the standards of their respective methyl esters (0.625 to 20 mg mL(-1)). Photosynthetic efficiency had significant differences for L. flavicans (0.31 +/- 0.01 to 0.38 +/- 0.01 mu mol e(-) m(-2) s(-1) (mu mol photons m(-2) s(-1))(-1)) and M. pyrifera (0.26 +/- 0.02 to 0.31 +/- 0.03 mu mol e(-) m(-2) s(-1) (mu mol photons m(-2) s(-1))(-1)) for reproductive and vegetative phases, respectively. The relative maximum electron transfer rate varied significantly for L. flavicans (8.10 +/- 0.84 to 12.40 +/- 1.57 mu mol e(-) s(-1)) and M. pyrifera (6.49 +/- 1.30 to 12.89 +/- 1.53 mu mol e(-) s(-1)) in distinct development phases. Saturation irradiance analysis showed significant differences for D. antarctica, varying from 166.18 +/- 14.33 (vegetative) to 132.98 +/- 18.43 mu mol photon m(-2) s(-1) (reproductive). The highest concentrations of pigments were found in reproductive M. pyrifera with 35.36 +/- 0.21 of Chl a, 7.04 +/- 0.93 of Chl c, and 15.75 +/- 1.42 mu g g(-1) of fucoxanthin. Finally, the highest concentrations of total FAs were 35.24 +/- 2.38% (saturated) and 22.02 +/- 1.95% (monounsaturated) in M. pyrifera and 63.53 +/- 3.36% (polyunsaturated) in D. antarctica. Therefore, the study showed significant differences for photosynthetic parameters and FA profiles correlating these results to the development phases of macroalgae.
Keywords: polyunsaturated; fatty acids; brown algae; photosynthetic activity; sub-antarctic region